Lignin-based hard carbon and preparation method thereof
By grafting dithioamino groups on lignin and loading cobalt ions, combining with scale graphite powder blending, the problem of insufficient performance of hard carbon anode materials in sodium ion batteries is solved, and higher rate performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202411934722.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The low efficiency, insufficient cycle stability and poor rate performance of existing hard carbon anode materials in sodium ion batteries hinder their industrial application.
By grafting the dithioamino group through the Mannich reaction and esterification reaction of alkali lignin, the electrochemical properties of lignin are improved, and the electron conductivity and Na+ transfer rate of hard carbon are enhanced by blending cobalt ion load and scale graphite powder.
The electrochemical properties of lignin-based hard carbon are significantly improved, including improving rate performance and cycling stability, and enhancing the adsorption capacity of sodium ions.
Smart Images

Figure BDA0005211217590000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lignin-based hard carbon and a preparation method thereof. Background Art
[0002] Hard carbon refers to carbon materials that are difficult to graphitize even at a high temperature of 2800°C. They are generally formed by sintering thermosetting precursors (oxygen-rich or hydrogen-deficient materials) such as biomass (wood, walnut shells, banana peels, etc.), sugars (glucose, sucrose, cellulose, etc.), and synthetic resins at high temperatures. Hard carbon has the advantages of low cost, easy preparation, low sodium storage potential, and high capacity. It is considered to be a negative electrode material for sodium ion batteries with commercial potential. However, due to the complex structure of hard carbon and the presence of many pores and defects, there are problems such as low first coulomb efficiency, insufficient cycle stability, and poor rate performance. These factors seriously hinder the industrial application of hard carbon negative electrode materials.
[0003] Lignin is a natural, renewable, aromatic-ring-rich polymer that is widely found in the xylem of plants, with an annual production of up to 150 billion tons worldwide. Lignin is a multi-level three-dimensional network structure composed of three phenylpropane monomers. At the same time, because of its functional groups such as phenolic hydroxyl, carboxyl, and methoxy, it can be used as a dispersant, surfactant, anti-ultraviolet agent, reinforcing agent, adhesive, water reducer, etc. In addition, lignin with low cost and high carbon content (50-80%) is an excellent precursor for the preparation of hard carbon materials. However, functional groups such as CO and CH are easily retained on the surface of lignin-based hard carbon materials, which increases the difficulty of forming a stable surface solid electrolyte membrane in the electrolyte, which can easily lead to a decrease in the initial charge and discharge efficiency.
[0004] Chinese patent publication CN115849332A discloses a high-rate hard carbon negative electrode material and a preparation method thereof. The method uses a biomass polymer as a hard carbon precursor, mixes it with anhydride organic matter through a solvent method, and utilizes the soft carbon properties of the anhydride organic matter to induce the hard carbon to grow a graphite microcrystalline structure and fill the hard carbon pores to form partial closed pores to increase the sodium storage capacity, thereby achieving high initial efficiency, high-rate performance and stable sodium ion storage, but its capacity is relatively low and still needs to be further improved. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a lignin-based hard carbon and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing lignin-based hard carbon, comprising the following steps:
[0008] S1. Add alkali lignin to deionized water, stir and dissolve, adjust the pH of the solution to 9-12, then add triethylenetetramine and formaldehyde, heat and stir to react, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 9-12, add carbon disulfide, stir and react for 2-4h, then filter, wash and dry to obtain modified lignin;
[0009] S2, placing the modified lignin in a cobalt salt solution, oscillating and adsorbing for 2-3 hours, and then filtering, washing, and drying to obtain cobalt-modified lignin;
[0010] S3, pre-carbonizing the cobalt-modified lignin under a protective atmosphere to obtain a carbonized material;
[0011] S4, dispersing the carbonized material in ethanol, then adding flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated, to obtain a composite powder;
[0012] S5. The composite powder is tableted and then carbonized under a protective atmosphere to obtain lignin-based hard carbon.
[0013] Specifically, in step S1, the mass ratio of alkali lignin, triethylenetetramine, formaldehyde and carbon disulfide is 10-15:4-8:10-20:3-5.
[0014] Specifically, in step S1, the temperature of the heating and stirring reaction is 75-90° C., and the time of the heating and stirring reaction is 3-5 h.
[0015] Specifically, in step S2, the mass ratio of the modified lignin to the cobalt salt solution is 8-12:100, and the mass fraction of the cobalt salt solution is 3-5%.
[0016] Specifically, in step S3, the pre-carbonization treatment temperature is 400-600° C., and the pre-carbonization treatment time is 1-3 hours.
[0017] Specifically, in step S4, the mass ratio of the carbonized material to the flake graphite powder is 10-15:2-4.
[0018] Specifically, in step S5, the pressure of the tableting process is 2-5 MPa, and the time of the tableting process is 10-20 min.
[0019] Specifically, in step S5, the carbonization treatment temperature is 800-900° C., and the carbonization treatment time is 1-3 hours.
[0020] In a second aspect, the present invention provides lignin-based hard carbon prepared by the above preparation method.
[0021] In a third aspect, the present invention also provides the use of the above-mentioned lignin-based hard carbon in battery negative electrode materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention first grafts triethylenetetramine onto the surface of lignin through the Mannich reaction, and then grafts dithioamino groups onto the surface of lignin through an esterification reaction. By grafting dithioamino groups onto the surface of lignin, on the one hand, the adsorption capacity of lignin for metal ions is increased, and on the other hand, by doping N and S elements into lignin, the electrochemical properties of lignin are improved.
[0024] (2) The present invention loads cobalt ions into lignin through the chelation effect of modified lignin on metal ions, thereby further improving the electrochemical properties of lignin. At the same time, the inventors found during the experiment that the electrochemical performance improvement effect of modified lignin loaded with cobalt ions is better than that of manganese ions and iron ions. The reason may be that the complexing ability of cobalt ions with modified lignin is stronger than that of manganese ions and iron ions, which helps to improve the dispersibility and stability of cobalt ions on modified lignin, thereby improving the electrochemical performance.
[0025] (3) The rate performance of hard carbon is related to the electronic conductivity of hard carbon itself and the Na + The speed of the transmission rate inside the hard carbon is related to the speed of the transmission rate. The present invention is beneficial to the improvement of electronic conductivity by blending the carbonized material and the flake graphite powder. At the same time, the layered structure of the flake graphite powder is beneficial to the Na + transport, thereby improving the electrochemical performance of lignin-based hard carbon. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0027] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0028] The present invention provides a method for preparing lignin-based hard carbon, comprising the following steps:
[0029] S1. Preparation of modified lignin
[0030] Add alkali lignin to deionized water, stir to dissolve, adjust the pH of the solution to 9-12, then add triethylenetetramine and formaldehyde, heat and stir to react, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 9-12, add carbon disulfide, stir to react for 2-4 hours, then filter, wash and dry to obtain modified lignin.
[0031] In this step, the mass ratio of alkali lignin, triethylenetetramine, formaldehyde and carbon disulfide is 10-15:4-8:10-20:3-5.
[0032] In this step, the temperature of the heating and stirring reaction is 75-90°C, for example, 75°C, 80°C, 85°C, and 90°C can be selected; the time of the heating and stirring reaction is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, and 5h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] In this step, triethylenetetramine is first grafted onto the surface of lignin through the Mannich reaction, and then dithioamino groups are grafted onto the surface of lignin through an esterification reaction. By grafting dithioamino groups onto the surface of lignin, on the one hand, the adsorption capacity of lignin for metal ions is increased, and on the other hand, the electrochemical properties of lignin are improved by doping N and S elements into lignin.
[0034] S2. Preparation of cobalt-modified lignin
[0035] The modified lignin is placed in a cobalt salt solution and subjected to oscillation adsorption for 2-3 hours, followed by filtration, washing and drying to obtain the cobalt-modified lignin.
[0036] In this step, the mass ratio of modified lignin to cobalt salt solution is 8-12:100. In some embodiments of the present invention, for example, 8:100, 9:100, 10:100, 11:100, 12:100 can be selected, but it is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0037] The mass fraction of the cobalt salt solution is 3-5%, for example, 3%, 4%, 5%, but not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Specifically, the cobalt salt can be selected from cobalt acetate, cobalt sulfate, cobalt nitrate or cobalt chloride.
[0039] In this step, cobalt ions are loaded into lignin through the chelation effect of modified lignin on metal ions, thereby further improving the electrochemical properties of lignin. At the same time, the inventors found during the experiment that the electrochemical performance improvement effect of modified lignin loaded with cobalt ions is better than that of manganese ions and iron ions. The reason may be that the complexing ability of cobalt ions with modified lignin is stronger than that of manganese ions and iron ions, which helps to improve the dispersibility and stability of cobalt ions on modified lignin, thereby improving the electrochemical performance.
[0040] S3. Pre-carbonization treatment
[0041] Under a protective atmosphere, the cobalt-modified lignin is pre-carbonized to obtain a carbonized material.
[0042] In this step, the pre-carbonization treatment temperature is 400-600°C, for example, 400°C, 450°C, 500°C, 550°C, and 600°C can be selected; the pre-carbonization treatment time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, and 3h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] S4. Preparation of composite powder
[0044] The carbonized material is dispersed in ethanol, and then flake graphite powder is added, dispersed evenly, heated and stirred until the ethanol is completely evaporated to obtain a composite powder.
[0045] In this step, the mass ratio of carbonized material to flake graphite powder is 10-15:2-4, for example, 10:2, 10:3, 10:4, 12:2, 12:3, 12:4, 15:2, 15:3, 15:4 can be selected; but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] The rate performance of hard carbon is related to the electronic conductivity of hard carbon and the Na + The speed of the transmission rate inside the hard carbon is related to the speed of the transmission rate. The present invention is beneficial to the improvement of electronic conductivity by blending the carbonized material and the flake graphite powder. At the same time, the layered structure of the flake graphite powder is beneficial to the Na + transport, thereby improving the electrochemical performance of lignin-based hard carbon.
[0047] S5. The composite powder is tableted and then carbonized under a protective atmosphere to obtain lignin-based hard carbon.
[0048] In this step, the tableting treatment pressure is 2-5MPa, for example, 2MPa, 2.5MPa, 3MPa, 3.5MPa, 4MPa, 4.5MPa, 5MPa can be selected; the tableting treatment time is 10-20min, for example, 10min, 15min, 20min can be selected, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] In this step, the carbonization treatment temperature is 800-900°C, for example, 800°C, 820°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, and 900°C can be selected; the carbonization treatment time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, and 3h can be selected, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] The present invention is further described below by means of specific examples. The alkali lignin used in the present invention is purchased from Wuhan Jiyesheng Chemical Co., Ltd.; the mesh number of the flake graphite powder is 2000 mesh.
[0051] Example 1
[0052] A method for preparing lignin-based hard carbon comprises the following steps:
[0053] S1. Add 10 g of alkali lignin to 150 g of deionized water, stir to dissolve, adjust the pH of the solution to 10, then add 4 g of triethylenetetramine and 10 g of formaldehyde, heat and stir to react at 75 ° C for 5 h, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 10, add 3 g of carbon disulfide, stir to react at room temperature for 3 h, then filter, wash and dry to obtain modified lignin;
[0054] S2, placing 8 g of modified lignin in 100 g of 3 wt% cobalt nitrate solution, shaking and adsorbing for 2 h, then filtering, washing and drying to obtain cobalt-modified lignin;
[0055] S3, in an argon atmosphere, pre-carbonizing the cobalt-modified lignin at a temperature of 400° C. for 3 h to obtain a carbonized material;
[0056] S4, dispersing 10 g of carbonized material in 150 mL of ethanol, then adding 2 g of flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated to obtain a composite powder;
[0057] S5. Place the composite powder in a tableting container for tableting treatment. The tableting pressure is 3 MPa and the tableting time is 15 min. Then, carbonization treatment is carried out under argon atmosphere. The carbonization temperature is 800° C. and the carbonization time is 3 h to obtain lignin-based hard carbon.
[0058] Example 2
[0059] A method for preparing lignin-based hard carbon comprises the following steps:
[0060] S1. Add 15g of alkali lignin to 150g of deionized water, stir to dissolve, adjust the pH of the solution to 10, then add 8g of triethylenetetramine and 20g of formaldehyde, heat and stir to react at 90°C for 3h, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 10, add 5g of carbon disulfide, stir to react at room temperature for 4h, then filter, wash and dry to obtain modified lignin;
[0061] S2, placing 12 g of modified lignin in 100 g of 3 wt% cobalt nitrate solution, oscillating and adsorbing for 3 h, then filtering, washing, and drying to obtain cobalt-modified lignin;
[0062] S3, in an argon atmosphere, pre-carbonizing the cobalt-modified lignin at a temperature of 600° C. for 1 h to obtain a carbonized material;
[0063] S4, dispersing 15 g of carbonized material in 150 mL of ethanol, then adding 4 g of flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated, to obtain a composite powder;
[0064] S5. Place the composite powder in a tableting container for tableting treatment. The tableting pressure is 2 MPa and the tableting time is 20 min. Then, carbonization treatment is carried out under argon atmosphere. The carbonization temperature is 900° C. and the carbonization time is 1 h to obtain lignin-based hard carbon.
[0065] Example 3
[0066] A method for preparing lignin-based hard carbon comprises the following steps:
[0067] S1. Add 12 g of alkali lignin to 150 g of deionized water, stir to dissolve, adjust the pH of the solution to 10, then add 6 g of triethylenetetramine and 15 g of formaldehyde, heat and stir to react at 80 ° C for 4 h, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 10, add 4 g of carbon disulfide, stir to react at room temperature for 3 h, then filter, wash and dry to obtain modified lignin;
[0068] S2, placing 10 g of modified lignin in 100 g of 3 wt% cobalt nitrate solution, oscillating and adsorbing for 3 h, then filtering, washing and drying to obtain cobalt-modified lignin;
[0069] S3, in an argon atmosphere, pre-carbonizing the cobalt-modified lignin at a temperature of 600° C. for 1 h to obtain a carbonized material;
[0070] S4, dispersing 12 g of carbonized material in 150 mL of ethanol, then adding 3 g of flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated to obtain a composite powder;
[0071] S5. The composite powder is placed in a tableting container for tableting treatment. The tableting pressure is 5 MPa and the tableting time is 20 min. Then, the composite powder is carbonized under an argon atmosphere at a temperature of 850° C. and a carbonization time of 2 h to obtain lignin-based hard carbon.
[0072] Comparative Example 1
[0073] A method for preparing lignin-based hard carbon comprises the following steps:
[0074] S1. Under an argon atmosphere, the alkali lignin is pre-carbonized at a temperature of 400° C. for 3 h to obtain a carbonized material;
[0075] S2, dispersing 10g of carbonized material in 150mL of ethanol, then adding 2g of flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated to obtain a composite powder;
[0076] S3. Place the composite powder in a tableting container for tableting treatment. The tableting pressure is 3 MPa and the tableting time is 15 minutes. Then, carbonization treatment is carried out under argon atmosphere. The carbonization temperature is 800°C and the carbonization time is 3 hours to obtain lignin-based hard carbon.
[0077] Compared with Example 1, Comparative Example 1 did not perform modification treatment on the lignin.
[0078] Comparative Example 2
[0079] A method for preparing lignin-based hard carbon comprises the following steps:
[0080] S1. Add 10 g of alkali lignin to 150 g of deionized water, stir to dissolve, adjust the pH of the solution to 10, then add 4 g of triethylenetetramine and 10 g of formaldehyde, heat and stir to react at 75 ° C for 5 h, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 10, add 3 g of carbon disulfide, stir to react at room temperature for 3 h, then filter, wash and dry to obtain modified lignin;
[0081] S2, placing 8 g of modified lignin in 100 g of 3 wt% ferric nitrate solution, oscillating and adsorbing for 2 h, then filtering, washing, and drying to obtain iron-modified lignin;
[0082] S3. Under an argon atmosphere, the iron-modified lignin is pre-carbonized at a temperature of 400° C. for 3 h to obtain a carbonized material;
[0083] S4, dispersing 10 g of carbonized material in 150 mL of ethanol, then adding 2 g of flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated to obtain a composite powder;
[0084] S5. Place the composite powder in a tableting container for tableting treatment. The tableting pressure is 3 MPa and the tableting time is 15 min. Then, carbonization treatment is carried out under argon atmosphere. The carbonization temperature is 800° C. and the carbonization time is 3 h to obtain lignin-based hard carbon.
[0085] Compared with Example 1, Comparative Example 2 uses ferric nitrate solution to replace the cobalt nitrate solution.
[0086] Comparative Example 3
[0087] A method for preparing lignin-based hard carbon comprises the following steps:
[0088] S1. Add 10 g of alkali lignin to 150 g of deionized water, stir to dissolve, adjust the pH of the solution to 10, then add 4 g of triethylenetetramine and 10 g of formaldehyde, heat and stir to react at 75 ° C for 5 h, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 10, add 3 g of carbon disulfide, stir to react at room temperature for 3 h, then filter, wash and dry to obtain modified lignin;
[0089] S2, placing 8 g of modified lignin in 100 g of 3 wt% manganese nitrate solution, oscillating and adsorbing for 2 h, then filtering, washing, and drying to obtain manganese-modified lignin;
[0090] S3. Under an argon atmosphere, the manganese-modified lignin is pre-carbonized at a temperature of 400° C. for 3 h to obtain a carbonized material;
[0091] S4, dispersing 10 g of carbonized material in 150 mL of ethanol, then adding 2 g of flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated to obtain a composite powder;
[0092] S5. Place the composite powder in a tableting container for tableting treatment. The tableting pressure is 3 MPa and the tableting time is 15 min. Then, carbonization treatment is carried out under argon atmosphere. The carbonization temperature is 800° C. and the carbonization time is 3 h to obtain lignin-based hard carbon.
[0093] Compared with Example 1, Comparative Example 3 uses manganese nitrate solution to replace cobalt nitrate solution.
[0094] Comparative Example 4
[0095] A method for preparing lignin-based hard carbon comprises the following steps:
[0096] S1. Add 10 g of alkali lignin to 150 g of deionized water, stir to dissolve, adjust the pH of the solution to 10, then add 4 g of triethylenetetramine and 10 g of formaldehyde, heat and stir to react at 75 ° C for 5 h, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 10, add 3 g of carbon disulfide, stir to react at room temperature for 3 h, then filter, wash and dry to obtain modified lignin;
[0097] S2, placing 8 g of modified lignin in 100 g of 3 wt% cobalt nitrate solution, shaking and adsorbing for 2 h, then filtering, washing and drying to obtain cobalt-modified lignin;
[0098] S3, in an argon atmosphere, pre-carbonizing the cobalt-modified lignin at a temperature of 400° C. for 3 h to obtain a carbonized material;
[0099] S4. The carbonized material is placed in a tabletting container for tabletting treatment. The tabletting pressure is 3 MPa and the tabletting time is 15 minutes. Then, the carbonization treatment is carried out under an argon atmosphere. The carbonization treatment temperature is 800°C and the carbonization treatment time is 3 hours to obtain lignin-based hard carbon.
[0100] Compared with Example 1, Comparative Example 4 does not add flake graphite powder.
[0101] The performance of the lignin-based hard carbon prepared in Examples 1-3 and Comparative Examples 1-4 was tested, and the specific steps were as follows:
[0102] First, the lignin-based hard carbon and superconducting carbon black prepared in Examples 1-3 and Comparative Examples 1-4 are respectively put into a ball mill and ball milled for 2 hours, and the speed is set to 200 r / min. Then, the binder polyvinylidene fluoride (PVDF) is dissolved in N-methylpyrrolidone (NMP). After complete dissolution, the ground sample is transferred to the solution and fully stirred for 4 hours, wherein the mass ratio of lignin-based hard carbon, superconducting carbon black and PVDF is 7:2:1, and NMP is added dropwise to make the slurry have a certain fluidity. The slurry is coated on copper foil with a coater, and after drying, it is transferred to a vacuum drying oven and dried at 120°C for 12 hours. The copper foil with the coated sample is rolled and cut into electrode sheets with a diameter of 12 mm. The mass of each electrode sheet is weighed and recorded, and then transferred to a vacuum oven and dried at 120°C for 12 hours. After cooling to room temperature, the electrode sheet is quickly put into a glove box for standby use. The sodium ion battery was assembled in a glove box filled with high-purity argon gas, and the oxygen and water content in the box was controlled to be less than 0.1 ppm during the operation. In the half-cell, a sodium sheet was used as the counter electrode and a 1 mol / L NaClO4 solution (the solvent was a mixed solution of diethyl carbonate and ethylene carbonate, with a volume ratio of 1:1) was used as the electrolyte to assemble an LIR2032 button cell for electrochemical performance testing.
[0103] The test was conducted on the Xinwei battery test system. The charge and discharge voltage range was 0-2V, the current density was 1C, 1C=100mA / g, and the test results are shown in the following table:
[0104]
[0105]
[0106] It can be seen from the table that the rate performance of the lignin-based hard carbon sodium ion battery negative electrode material prepared in the embodiment of the present invention is significantly improved, and the capacity retention rate can still reach more than 90% after 100 cycles at a current density of 1C.
[0107] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A method for preparing lignin-based hard carbon, characterized in that: The steps include: S1. Add alkali lignin to deionized water, stir and dissolve, adjust the pH of the solution to 9-12, then add triethylenetetramine and formaldehyde, heat and stir to react, after the reaction is completed, cool to room temperature, adjust the pH of the solution to 9-12, add carbon disulfide, stir and react for 2-4h, then filter, wash and dry to obtain modified lignin; S2, placing the modified lignin in a cobalt salt solution, oscillating and adsorbing for 2-3 hours, and then filtering, washing, and drying to obtain cobalt-modified lignin; S3, pre-carbonizing the cobalt-modified lignin under a protective atmosphere to obtain a carbonized material; S4, dispersing the carbonized material in ethanol, then adding flake graphite powder, dispersing evenly, heating and stirring until the ethanol is completely evaporated, to obtain a composite powder; S5. The composite powder is tableted and then carbonized under a protective atmosphere to obtain lignin-based hard carbon.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of alkali lignin, triethylenetetramine, formaldehyde and carbon disulfide is 10-15:4-8:10-20:3-5.
3. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the heating and stirring reaction is 75-90° C., and the time of the heating and stirring reaction is 3-5 h.
4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the modified lignin to the cobalt salt solution is 8-12:100, and the mass fraction of the cobalt salt solution is 3-5%.
5. The preparation method according to claim 1, characterized in that: In step S3, the pre-carbonization treatment temperature is 400-600° C., and the pre-carbonization treatment time is 1-3 hours.
6. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the carbonized material to the flake graphite powder is 10-15:2-4.
7. The preparation method according to claim 1, characterized in that: In step S5, the tableting process is performed at a pressure of 2-5 MPa and for a time of 10-20 min.
8. The preparation method according to claim 1, characterized in that: In step S5, the carbonization treatment temperature is 800-900° C., and the carbonization treatment time is 1-3 hours.
9. The lignin-based hard carbon prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the lignin-based hard carbon as claimed in claim 9 in battery negative electrode materials.
Citation Information
Patent Citations
High-rate hard carbon negative electrode material and preparation method and application thereof
CN115849332A
Cited By
Hard carbon negative electrode material, preparation method thereof and negative electrode
CN121158762A